Concomitant Central Giant Cell Granuloma and Aneurysmal Bone Cyst in a Young Child - Deepika Pai; Abhay Taranath Kamath; Adarsh Kudva; Monica Monica Charlotte Solomon; Saurabh Kumar; Prem Sasikumar (Case Reports in Dentistry)
Although Central Giant Cell Granuloma (CGCG) is a benign tumor of the jaw and aneurysmal bone cyst seen in children, its aggressive behavior causes extensive loss of hard tissue requiring wide excision and extensive rehabilitation. We report a rare case of concomitant CGCG and aneurysmal bone cyst in a two-year-old male child, involving the coronoid and condylar process. Young age, large tumor, its aggressive nature, and future growth of orofacial region pose a significant challenge in the management of such conditions. For a successful outcome, the systematic approach to the presurgical evaluation and appropriate treatment planning is essential for such conditions.